Epileptic negative myoclonus in herpes simplex virus encephalitis. Issue 2 (7th June 2022) - Fotedar, Neel; Dolbow, James; Layfield, Madhura; Thyagaraj, Suraj; Zande, Jonathan
Abstract: Epileptic negative myoclonus (ENM) is a rarely reported clinical seizure semiology. It is defined as a brief interruption of tonic muscle activity in association with an epileptiform discharge on the EEG (spike or sharp wave) without preceding myoclonia. The diagnosis of ENM requires a polygraphic recording with EEG and surface EMG electrodes covering the affected body part(s), while the muscles have tonic activity. Historically, ENM has been reported in a variety of chronic epilepsy syndromes such as benign epilepsy with centrotemporal spikes, progressive myoclonic epilepsy syndromes, symptomatic partial epilepsy syndromes due to structural pathologies, cryptogenic epilepsies, etc . In this paper, we report a patient with herpes simplex virus encephalitis who presented with multiple different seizure types including ENM. The patient showed significant improvement after treatment with acyclovir.